Carbon-Based Solid Acid Pretreatment in Corncob Saccharification: Specific Xylose Production and Efficient Enzymatic Hydrolysis - Wei Qi (2018)
© Copyright 2018 American Chemical Society. In this paper, we disclose a novel saccharification technology for lignocellulosic biomass. A new carbon-based solid (C-SO3H) acid catalyst was first synthesized by a simple, one-step hydrothermal carbonization method using microcrystalline cellulose and sulfuric acid. The functional group, chemical composition and structure of the catalyst were characterized. After five reuses, the solid acid catalyst still showed a high catalytic activity for corncob pretreatment. Under optimal pretreatment conditions (140 °C, 6 h, 0.25 g of corncob, 0.25 g of catalyst, and 25 mL of water), xylose was directly released from corncob in a high yield (78.1%). Enzymatic hydrolysis of the pretreatment residue provided an enzymatic digestibility of up to 91.6% in 48 h. The structure, morphology, and components of the corncob and residues were analyzed. The high xylose and glucose yields confirmed the high catalytic activity of the synthetic carbon-based solid acid, providing green and effective lignocellulose utilization.